Trade Policies and Entrepreneurial Initiatives: A Nexus for India’s Global Market Integration - Khair, Md Abul; Tejani, Jayadip GhanshyamBhai; Sandu, Arun Kumar; Shajahan, Mohamed Ali (American Journal of Trade and Policy, 2020)
In the context of India’s integration into global markets, this study investigates the relationship between India’s trade policies and its entrepreneurial efforts. The primary objectives are to examine the impact of trade policies on entrepreneurship, analyze how entrepreneurial activities influence the design of trade policies, identify mechanisms that support India’s integration into global markets, and provide policy suggestions. This study analyzes scholarly articles, government publications, and industry reports using an approach based on examining secondary data. The most important findings shed light on the mutually beneficial link between trade policies and entrepreneurial endeavors, the significance of trade liberalization for market access, and export-oriented entrepreneurship’s role in India’s integration into global commercial markets. In the context of policy implications, the necessity for holistic policy approaches, flexibility in policy design, measures to build capacity for entrepreneurs, involvement with stakeholders, and constant monitoring and evaluation is emphasized. Through this nexus, India has the potential to open up opportunities, improve its competitiveness, and establish itself as a significant player in the world economy.